TRANSITIVITY OF CONSUMER PREFERENCE: A COMPARISON BETWEEN CATEGORIES OF SELECTED VARIABLES - Sacay, Marciano T.; Alkuino Jr., Jose M. (Annals of Tropical Research, 1986)
The study relates the consistency of choice and preference among Filipino consumers to selected variables. One hundred twenty-four respondents categorized into high school students, college students, professionals and farmers were included in the survey. Transitivity of responses were compared among categories of variables such as age, sex, occupation, education and civil status. Significant differences across categories of all variables except age were observed. Professionals, college graduates, and females had the highest transitivity of responses under categories of occupation, education and sex, respectively.